An Analysis of The Implementation Project Based Learning In The English Reading Class of Eleventh Grade Students At SMA 3 Kota Bengkulu - Sari, Arum Mutiara (The Future of Education Journal, 2026)
This study aims to analyze the implementation of Project-Based Learning (PjBL) in English reading instruction for eleventh-grade students at SMA Negeri 3 Kota Bengkulu, focusing on instructional practices, student engagement, assessment, and contextual challenges. The study addresses the ongoing issue of teacher-centered reading instruction in EFL classrooms, which often limits students’ engagement and higher-order comprehension skills. A qualitative descriptive case study design was employed to obtain an in-depth understanding of the phenomenon. Data were collected through classroom observations, semi-structured interviews with two English teachers and selected eleventh-grade students, and document analysis of lesson plans, reading materials, student projects, and assessment instruments. The data were analyzed using thematic analysis following the interactive model of data reduction, data display, and conclusion drawing.The findings reveal that PjBL was implemented through structured stages, including contextual problem introduction, guided reading, collaborative discussion, project construction, and assessment. The approach enhanced students’ reading engagement, comprehension, and ability to synthesize textual information into meaningful products. Reading activities became more purposeful and contextualized, fostering collaboration, creativity, and critical thinking. However, challenges related to limited instructional time, variation in students’ reading proficiency, and the absence of comprehensive assessment rubrics were also identified.The study concludes that Project-Based Learning can effectively transform reading instruction into a student-centered and meaningful learning process when supported by careful instructional planning and appropriate assessment strategies. These findings contribute to EFL pedagogy by providing contextual insights into PjBL implementation and offer implications for teaching practice and future research in reading instruction